Appreciation should be EA-SI—demystifying the definition and operationalization of experienced appreciation at work by developing a new construct - Resch, Maximilian; Bellhäuser, Henrik (Frontiers in Psychology, 2025)
In this article, we developed the new construct, Experienced Appreciation in Social Interactions (EA-SI), to reduce the inconsistency in defining and measuring experienced appreciation at work. The integrative theoretical model is based on the well-validated Stress as Offense to Self-theory. To operationalize the construct, we validated the EA-SI Work Scale in two independent German samples of employees. Colleagues and supervisors were investigated as potential sources of experienced appreciation. Study One included N = 231 participants. Study Two encompassed N = 391. In both studies, we applied a cross-sectional field-study design based on self-reported surveys. Using exploratory and confirmatory factor analyses, the construct EA-SI turned out to be unidimensional. The Pearson product-moment correlations showed that the more employees felt appreciated, the higher their self-esteem and the lower their stress perception. The premises of the theoretical foundation were replicable. Higher experienced appreciation was related to more work satisfaction, life satisfaction, and work engagement, as well as lower emotional exhaustion. These relations were true for both groups of appreciators. When tested in hierarchical regressions, EA-SI added incremental prediction beyond the influence of social support in most of the analyses. The instrument's internal consistency and retest reliability were good to excellent. The results indicated the EA-SI Work Scale to be content, construct, and criterion valid. Based on these findings, the strengths and limitations of the article and possible implications for future research and practical use are discussed.